METHODS FOR EVALUATION OF COMPANIES’ INFORMATION SYSTEMS AND TECHNOLOGIES EFFICIENCY AND CONTROL IN TEACHING COURSE "INFORMATION TECHNOLOGY GOVERNANCE" (Journal of Information Technologies in Education (ITE), 2015)
The use of the information systems and technologies in economic activity is called to represent companies’ corporate principles, aims, traditions, to help in realization of the planned strategies, thanks to that the management efficiency and the cost of enterprise increases. Teaching for educational discipline «IT Governance» is directed on a study and research of these intercommunications by students of the 5th course on specialties «Computer Science», «Software Engineering» for educational level Specialist (Past Bachelor Degree), Master degree.     The auditing services belong to the actual methods for evaluation of the information systems and technologies efficiency and control, which are studied according to the course «IT Governance». The article deals with the methodological basis of providing auditing services for evaluation of efficiency and control of information systems (technologies) for the purpose of satisfaction of growing informational needs of companies and functional activation in their information resources. The main task of auditing services for control of information systems (information communication technologies) efficiency is to evaluate independently and objectively if the information technologies provide the necessary services. The basic criteria, data ware, subject and object of audit necessary for drawing up an audit report and assurance declaring are established.The program and a detailed list of auditing procedures for evaluation of efficiency of information systems and technologies have been presented.
Keywords: information technologies; companies; evaluation of efficiency; information technology governance; auditing services; control